Effect of Translational Signals on mRNA Decay in Bacillus subtilis - Sharp, Josh S. (American Society for Microbiology, 2003)
A 254-nucleotide model mRNA, designated ΔermC mRNA, was used to study the effects of translational signals and ribosome transit on mRNA decay in Bacillus subtilis. ΔermC mRNA features a strong ribosome-binding site (RBS) and a 62-amino-acid-encoding open reading frame, followed by a transcription terminator structure. Inactivation of the RBS or the start codon resulted in a fourfold decrease in the mRNA half-life, demonstrating the importance of ternary complex formation for mRNA stability. Data for the decay of ΔermC mRNAs with stop codons at positions increasingly proximal to the translational start site showed that actual translation—even the formation of the first peptide bond—was not important for stability. The half-life of an untranslated 3.2-kb ΔermC-lacZ fusion RNA was similar to that of a translated ΔermC-lacZ mRNA, indicating that the translation of even a longer RNA was not required for wild-type stability. The data are consistent with a model in which ribosome binding and the formation of the ternary complex interfere with a 5′-end-dependent activity, possibly a 5′-binding endonuclease, which is required for the initiation of mRNA decay. This model is supported by the finding that increasing the distance from the 5′ end to the start codon resulted in a 2.5-fold decrease in the mRNA half-life. These results underscore the importance of the 5′ end to mRNA stability in B. subtilis.